2021
DOI: 10.1371/journal.pone.0250793
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 social-distancing on sleep timing and duration during a university semester

Abstract: Social-distancing directives to contain community transmission of the COVID-19 virus can be expected to affect sleep timing, duration or quality. Remote work or school may increase time available for sleep, with benefits for immune function and mental health, particularly in those individuals who obtain less sleep than age-adjusted recommendations. Young adults are thought to regularly carry significant sleep debt related in part to misalignment between endogenous circadian clock time and social time. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
(39 reference statements)
4
31
1
1
Order By: Relevance
“…In general, studies worldwide described a shift to later bedtime and rise time during the quarantine period (Cellini et al, 2020 ; Gupta, 2020 ; Wright et al, 2020 ). Also, the reduced sunlight exposure may have concurred to the reduction of the externally imposed sleep‐wake rhythms (Smit et al, 2021 ). However, we should consider that the increase in time spent in bed was not paralleled by the same rise of the effective sleeping time.…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies worldwide described a shift to later bedtime and rise time during the quarantine period (Cellini et al, 2020 ; Gupta, 2020 ; Wright et al, 2020 ). Also, the reduced sunlight exposure may have concurred to the reduction of the externally imposed sleep‐wake rhythms (Smit et al, 2021 ). However, we should consider that the increase in time spent in bed was not paralleled by the same rise of the effective sleeping time.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for exclusions were 1) age below 18 (n = 18 participants); 2) shift in MSFsc >4 hours (n = 78 participants) as expected changes in MSFsc were estimated to be around 30 minutes with a SD between 1:15 and 1:45. 44,45 This 4h value (>30 min + 2 SD) allowed to exclude outliers mainly due to misunderstandings (eg, we noticed that some participants had recorded bedtimes and wake-up times in 12-hour instead of 24-hour format), a table is provided with characteristics of these outliers (Supplementary Table 1); The final sample consisted of 2513 participants, among which 285 were excluded from the multivariate analysis because of missing data for the main outcome or at least one of the adjustment variables.…”
Section: Resultsmentioning
confidence: 99%
“…The population consisted of 77% women, of median (IQR) age 39 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) years. Two-thirds of participants were employees with daytime working hours before the confinement and worked from home during the lockdown.…”
Section: Characteristics Of the Populationmentioning
confidence: 99%
“…These findings of a later and longer sleep during weekdays, thus reducing social jetlag, corroborate previous studies performed during the lockdown: Leone et al found a 36-minute delay in MSFsc in the Argentina’s population 44 and Smit et al reported a 30-minute delay in sleep schedule in Canadian students. 45 Such change in sleep-wake rhythm during the week may be related to the fact that most participants of our study worked from home during the lockdown, with more flexible schedules and a decrease in exposure to external synchronizers such as outdoor daylight and social constraints. 22 It may also result from the psychological distress linked to the pandemic.…”
Section: Discussionmentioning
confidence: 97%